2016
DOI: 10.1606/1044-3894.2016.97.3
|View full text |Cite
|
Sign up to set email alerts
|

Teenage Pregnancy in Latino Communities: Young Adult Experiences and Perspectives of Sociocultural Factors

Abstract: Racial and ethnic inequities persist in teenage pregnancy rates, prompting examinations of how to provide better attuned teen pregnancy prevention in key affected communities. The current study focused on sociocultural factors of teen pregnancy in Latino communities, using in-depth, semi-structured qualitative interviews to elicit the experiences and perspectives of young adult Latino/as (some who prevented and others who directly experienced teen pregnancy in their own lives). Using a grounded theory approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In the U.S., research to identify the risk factors explaining high rates of adolescent pregnancy disproportionately affecting racial/ethnic minorities, including Latinas, have largely focused on social and cultural factors that influence girls' pregnancy intentions and decisions regarding the use of contraception, as well as girls' sexual and reproductive decision-making control in relationships [10,11]. Norms supportive of adolescent or early pregnancy and negative attitudes towards condom and other contraceptive use have been highlighted as important contributors to adolescent pregnancy [12,13]. Furthermore, intimate partner violence (IPV), which has been reported in up to 20% of adolescent girls, is associated with reduced sexual/reproductive autonomy (i.e., sexual and contraceptive decision-making power) among girls, and in turn, increases risk for both STI and pregnancy [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S., research to identify the risk factors explaining high rates of adolescent pregnancy disproportionately affecting racial/ethnic minorities, including Latinas, have largely focused on social and cultural factors that influence girls' pregnancy intentions and decisions regarding the use of contraception, as well as girls' sexual and reproductive decision-making control in relationships [10,11]. Norms supportive of adolescent or early pregnancy and negative attitudes towards condom and other contraceptive use have been highlighted as important contributors to adolescent pregnancy [12,13]. Furthermore, intimate partner violence (IPV), which has been reported in up to 20% of adolescent girls, is associated with reduced sexual/reproductive autonomy (i.e., sexual and contraceptive decision-making power) among girls, and in turn, increases risk for both STI and pregnancy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found Hispanic/Latina mothers to be more likely to have a repeat pregnancy than other racial/ethnic groups (Patel et al, 1997; Pfitzner et al, 2003), so it is particularly important to understand predictors of teen pregnancy for these mothers (Bouris et al, 2012). Although Hispanic/Latino mothers in the United States are diverse in terms of their country of origin, access to resources, and history and experiences (Beaglehole, 2003; Pew Hispanic Center, 2009), “there appear to be some shared traditional values and experiences in the U.S. Latino population that affect teenage pregnancy, such as the value of motherhood and the influence of family and family communication” (Aparicio et al, 2016, p. 2). These values may mean that some predictors of repeat pregnancy are unique among this group.…”
Section: Social Ecological Theorymentioning
confidence: 99%
“…Research on parent/adolescent communication has focused on youth perceptions [15]. Studies on parental perspectives have investigated mother-daughter versus father-son communication on sexuality [15,16].…”
mentioning
confidence: 99%
“…Research on parent/adolescent communication has focused on youth perceptions [15]. Studies on parental perspectives have investigated mother-daughter versus father-son communication on sexuality [15,16]. While research on paternal communication about sexuality with teenage sons has increased, less is known about paternal interaction that prevent risky behavior among daughters and sons in Hispanic families especially in rural areas [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation